ANALISIS PENGARUH RASIO LIKUIDITAS, SOLVABILITAS TERHADAP HARGA SAHAM PT. INDOFOOD CBP SUKSES MAKMUR Tbk - Devi Krisnawati; Ilham Setiawan; Elsa Ari Setya Anjani (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2018)
This study aim to analyze the influence of liquidity ratio and solvabily to stock price of PT Indofood CBP Sukses Makmur. This research used quantitative research method with secondary data collection techniques. In this study, data was obtained by accessing the Indonesia Stock Exchange gallery website to obtain documents in the form of financial statements of PT. INDOFOOD CBP SUKSES MAKMUR Tbk. listed on the Indonesia Stock Exchange in accordance with the provisions of the writing. This research using multiple linear regression analysis techniques as the data analysis techniques. The capital market in Indonesia currently shows developments in the Indonesian economy. This rapid development occurred because of the increasing public interest in investing in the capital market, the development of public knowledge about the capital market, and the increasing number of companies registered in the capital market. The advantage of a company from investments made is one of the important factors that must be considered in making investments, because it affects stock prices. Variations in stock prices are influenced by various factors both internal and external factors. There are two analyzes that can be used to anticipate the risks arising from stock prices that change every time, fundamental security analysis or company analysis and technical analysis. Fundamental analysis tries to calculate the intrinsic value of a stock by using company financial data or ratios, including with liquidity ratios and solvency ratios. The liquidity ratio is to show or measure the ability of a company to meet its maturing obligations. In this study the ratio used to measure the level of corporate liquidity is Current Ratio. Solvency ratio is the ratio of the company's ability to fulfill its financial obligations. In this study the solvency ratio used is Debt to Equity Ratio. Based on the results of this study it can be concluded that the Variable Current Ratio (CR) and Debt to Equity Ratio (DER) simultaneously do not have a significant effect on Stock Prices; Current Ratio (CR) variable has a negative but significant effect on Return on Equity (ROE); and the Debt to Equity Ratio (DER) variable partially has a positive and insignificant effect on stock prices.